Basic Profile of Early Childbirth in Niger - Malé, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of early childbirth in Niger. Measures of early childbirth are high. The share of women ages 18-22 who had their first child before 18 is 47.1 percent and it has slightly increased over time. The share of women with their first child before 15 is at just under 10 percent. Other measures of early childbirth have also not declined, with increases in some cases over the last 25 years. Early childbirth is associated with lower wealth and lower education levels, and employment without cash earnings. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.